Reimagining Tradition: How Tourist Generation Z Perceives Modern Twists on Yogyakarta’s Bakpia - Suci Sandi Wachyuni; Kadek Wiweka; Nicko Gana Saputra (Journal of Tourism and Economic, 2025)
Generation Z is highly susceptible to the influences of globalization, particularly in shaping their purchasing preferences. This phenomenon extends to the food and beverage industry, where traditional culinary practices undergo modifications to align with contemporary tastes. One such example is bakpia, a renowned traditional pastry from Yogyakarta. Recognizing this trend, the present study seeks to explore the perceptions of Generation Z tourists regarding the modern adaptations of bakpia in Yogyakarta. Employing a quantitative research approach, data were collected through questionnaire distribution, targeting Generation Z tourists as the primary respondents. A purposive sampling technique was applied, yielding a total sample of 108 respondents. The collected data were analyzed using descriptive statistical methods. Findings indicate that Generation Z tourists exhibit a stronger preference for modified versions of bakpia over its original form. Among the key product attributes assessed, menu variety emerged as the most influential factor, followed by product quality, price, taste, information availability, and cleanliness. Conversely, portion size ranked lowest in influencing purchase decisions. By understanding Generation Z tourists’ perceptions of bakpia modifications, this study provides valuable insights into tourist behavior and offers strategic recommendations for entrepreneurs in the food and beverage sector—particularly those specializing in traditional bakpia production. The findings highlight opportunities for business innovation, enabling culinary enterprises to enhance their offerings in response to evolving consumer preferences. This study is original and contributes novel insights, as previous research has not specifically examined Generation Z tourists’ perceptions of traditional pastry modifications in Yogyakarta. Prior studies have largely focused on broader generational comparisons or general tourist perceptions rather than honing in on a single traditional delicacy. Thus, this research bridges a critical gap in the literature and offers a foundation for future explorations in the intersection of globalization, culinary adaptation, and generational consumer behavior.